Implementation of Problem-Based Learning Model on Basic Acid Basic Material to Develop Student Character Values XI IPA 3 SMA Negeri 1 Parepare - Munandar, Haris; Syam, Hijrah (Sainsmat : Jurnal Ilmiah Ilmu Pengetahuan Alam, 2017)
This research is a Classroom Action Research that aims to find out how the problem-based learning steps so as to develop the student's character values. The subjects of this study were students of Class XI IPA 3 SMA Negeri 1 Parepare with 39 students. This research was conducted in two cycles, each cycle consisting of planning, implementation, observation / evaluation, and reflection. Each cycle consists of four meetings, three meetings for teaching and learning and one evaluation meeting. Data collection was done by using observation sheet of student activity/activity, observation sheet of student character and student character questionnaire and analyzed qualitatively. Based on the results of descriptive statistical analysis for student learning outcomes on the show that the cycle I obtained an average value of 67.02 whereas in cycle II obtained an average value of 75.61. Questionnaires and observation sheets are used to observe the character development of students. By applying the steps of the problem-based learning model, the character of the student develops based on the observation result and student character questionnaire which increases from cycle I to cycle II.